Projek penswastaan Lebuhraya Bertingkat Sg Besi – Ulu Klang (SUKE): infrastructure industrial area and used car / Abdul Muhaimin Husain - Husain, Abdul Muhaimin (2017)
This report in explains on how to do dilapidation survey. Topic that I choose for this report is infrastructure at the industrial area and used car area Sg Besi, Selangor. This dilapidation survey needs to do before new construction start. This report produced refer for undergone practical training in HytechEMPIRE CONSULTANCY SDN.BHD, Bandar Seri Putra, Kajang, Selangor. This report divided into six chapters that starting with company profile. Then it follows with theoretical review about dilapidation survey for infrastructure. After that, case study during practical training. Then, problem and recommendation follow by conclusion and lastly references. This report concludes with conclusion and recommendation that can be ensured during undergone practical training. In conclusion, this report able to explain overall on certificate of fitness.